Autonomic Function in Parkinson's Disease Subjects Across Repeated Short-Term Dry Immersion: Evidence From Linear and Non-linear HRV Parameters - Gerasimova-Meigal, Liudmila; Meigal, Alexander; Sireneva, Nadezhda; Saenko, Irina (Frontiers in Physiology, 2021)
Several studies have shown that “dry” immersion (DI) appears as a promising method of rehabilitation for Parkinson’s disease (PD). Still, little is known on the cardiovascular reaction on DI, especially in PD. Therefore, this study was aimed at evaluating the effect of repeated 45-minute DI sessions on autonomic function in subjects with PD. 20 subjects with PD (13men, 7 women, aged 51-66 years, H&Y staged 1-3) were enrolled to the study according to inclusion and non-inclusion criteria. The DI program was comprised of seven 45-minute DI sessions, applied within 25-30 days. Blood pressure (BP), heart rate (HR) and ECG in the standard lead II were recorded at 1st, 4th and 7th DI, before, on the 15th, 30th and 40th min of DI session. Autonomic function was assessed with analysis of heart rate variability (HRV) using Kubios Standard v2.0 software. Linear (time- and frequency-domain) and nonlinear (correlation dimension, entropies, DFA1 and DFA2, percent of determinism and recurrence) were computed. At baseline condition, time- and frequency-domain HRV parameters showed low variability of HR, what indicates on reduced autonomic neurogenic control of HR. Throughout the DI session, systolic and diastolic BP has decreased by 5-7 mm Hg (p<0,001), and time- and frequency-domain parameters of HRV have significantly increased, what can be regarded as compensatory mechanisms of hemodynamics during DI. The structure of the regulatory input to the heart seen by HRV was characterized by low complexity and reduced autonomic neurogenic control of HR. Across the program of DI sessions, the hypotensive effect was documented, but no notable modification of the HRV-parameters was found. The absence of long-term modification of the studied parameters can be attributed both to deconditioning environmental effect of DI and limited adaptation of the organism due to neurodegeneration in PD. That should be taken into consideration when planning rehabilitation measures in subjects of older age and chronic somatic diseases with modeled microgravity.